2018
DOI: 10.1111/bjh.15543
|View full text |Cite
|
Sign up to set email alerts
|

ACS in children with sickle cell anaemia in Uganda: prevalence, presentation and aetiology

Abstract: ACS (ACS) is a serious complication of sickle cell anaemia (SCA). We set out to describe the burden, presentation and organisms associated with ACS amongst children with SCA attending Mulago Hospital, Kampala, Uganda. In a cross-sectional study, 256 children with SCA and fever attending Mulago Hospital were recruited. Chest X-rays, blood cultures, complete blood count and sputum induction were performed. Sputum samples were investigated by Ziehl-Nielsen staining, culture and DNA polymerase chain reaction (PCR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…'s study, which reported a median WBC count of 24.9 k/μL (IQR, 18.1–29.8 k/μL). [ 20 ] Besides, Jaiyesimi and Kasem reported a mean value of WBC at ACS of 15.37 ± 8.39 k/μL (compared to 10.73 ± 3.00 k/μL at steady-state), and Al-Dabbous reported a mean WBC count of 17.8 k/μL at the time of ACS (compared to 11.4 k/μL at baseline). [ 13 ] The observed elevated level of WBC count can be attributed to infections being the common causes of ACS, especially among children.…”
Section: Discussionmentioning
confidence: 99%
“…'s study, which reported a median WBC count of 24.9 k/μL (IQR, 18.1–29.8 k/μL). [ 20 ] Besides, Jaiyesimi and Kasem reported a mean value of WBC at ACS of 15.37 ± 8.39 k/μL (compared to 10.73 ± 3.00 k/μL at steady-state), and Al-Dabbous reported a mean WBC count of 17.8 k/μL at the time of ACS (compared to 11.4 k/μL at baseline). [ 13 ] The observed elevated level of WBC count can be attributed to infections being the common causes of ACS, especially among children.…”
Section: Discussionmentioning
confidence: 99%